Trends in parasuicide and unemployment among men in Edinburgh, 1968-82. - Platt, S (1984)
Between 1968 and 1982 annual unemployment and annual incidence of parasuicide among men in Edinburgh were positively and highly significantly correlated (r = 0.77). Similarly, they were found to be correlated across the city wards in 1971 (r = 0.76) and, even more strongly, 1981 (r = 0.95). Throughout the period the incidence of parasuicide among the unemployed was nearly always more than 10 times higher than among the employed. Men unemployed for more than a year were at much higher risk than those out of work for shorter periods. These findings were considered to be consistent with the view that unemployment, especially if long term, increases the incidence of parasuicide. The official prediction of an increase in long term unemployment has important implications.